Issues and challenges of primary education toward implementing technical and vocational education training to meet the fourth industrial revolution demand: A systematic literature review - Maidin, Shajahan; Mohd Ali, Latifah; Kamarudin, Mohd Fauzi; Ismail, Shafinaz (Universiti Putra Malaysia Press, 2024)
The present wave of the fourth industrial revolution (4IR) technology and trends is drastically affecting nearly every economic sector and preparing for profound changes in people’s lives. The benefits of the technology include higher safety, better decision making, increased productivity, efficiency, and quality in processes, as well as increased competitiveness. Thus, every effort towards raising awareness of the 4IR should begin early in primary education. This study critically evaluated the literature on the issues and challenges of implementing Technical Vocational Education and Training (TVET) preliminary courses in primary education in Malaysia towards raising awareness of the future 4IR. Using two databases, namely Scopus and Web of Science, the review was conducted in accordance with the ROSES (Reporting Standards for Systematic Evidence Syntheses) publishing standard. The findings showed that the role of primary education in facilitating skills development for socio-economic and technological development for the students was significant. Based on the thematic analysis, two primary themes emerged: a lack of 21st-century skills and support, supplemented by six sub-themes. In addition, the issues and challenges of other countries’ primary education in meeting the 4IR demand are also discussed. The paper offered solutions for the issues that arose to fulfil the objective of TVET preparatory courses: to increase pupil awareness of the present 4IR in elementary education in Malaysia.